Reestruturação e automação de processos: caso de um processo da área de compras e suprimentos de uma empresa brasileira do setor de mídia - Toniato, Cintia Cristina Medeiros [UNESP] (2015)
Innovation in the field of Information Technology (IT) have made companies evaluate their processes and activity of its supply chain to conform to this new reality. In the supply chain management, one of the tools that revolutionized the activities was the use of management information systems such as ERP tool. This system allows greater integration of data from multiple areas of the enterprise and beyond, giving more activities to processes and activities. This work aims to analyze the results and impacts of the restructuring of an equipment leasing process in a Brazilian media company and verify that the gains and improvements that were targeted in the initial design of this restructuring have been achieved. Also the risks identified with this change will be studied, the reactions of those involved in this process and the performance of the chain as a whole. To carry out this work was carried out a single case study with data collection in the assessed company and literature related to supply chain and information systems